The Effect Of 7E Learning Cycle Model toward Student’s Learning Outcomes of Basic Science Concept - Marfilinda, Riri; Rossa, Rona; Jendriadi, Jendriadi; Apfani, Sry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study aims to investigate the effect of the application of the 7E (Elicit, Engange ,Explore, Explain, Elaborate, Evaluation and Extend) Learning Cycle Model to the learning outcomes of the Basic Science Concepts of second grade student of Elementary School. This research is a quasi-experimental study with a randomized pretest-posttest control group design. The population of this study was all students of Primary Teacher Education in higher educational private university college in Padang in the 2018/2019 school year. The sample consisted of 24 control class students and 28 experimental class students. The experimental class uses the 7E Learning Cycle model while the control class uses the conventional model. The data collection technique is in the form of a learning outcome test (cognitive). From this study, there were differences in student learning outcomes using learning with the learning model Cycle 7E with conventional learning. Learning with 7E Learning Cycle model gives an effect of 72% (moderate) to the improvement of student learning outcomes in the Basic Science Concept Course.